In-situ assessment of fire-damaged concrete and concrete members using direct ultrasonic pulse velocity technique - Concepcion, Dyke Jetrie C.
Before devising a restoration plan for fire-damaged structures, it is necessary to obtain relevant data on the structural adequacy of the building. The use of Ultrasonic Pulse Velocity (UPV) technique in combination with other NDT for fire-damage detection and assessment of fire-damaged concrete is presented in this paper. The main objective of the study is to determine the correlation between UPV from core samples and residual strength of in-situ fire-damaged concrete. To carry-out the NDT evaluation, preliminary procedures are required: strategic planning, preliminary investigation, condition survey, material property evaluation, and load test. to calibrate the UPV equipment, UPV test were carried out on the external surface of the undamaged concrete column of the building which was then used for subsequent analysis of how fire affects the response of the UPV on fire-damaged columns. Core samples were taken each from undamaged, slightly damaged, and highly damaged columns of the building. Information on the residual strength of fire-damaged concretes and depth of damage were obtained from compressive strength test and application of UPV test respectively.